Fifty-Two-Week Results of Clinical and Imaging Assessments of a Patient with Rheumatoid Arthritis Complicated by Systemic Sclerosis with Interstitial Pneumonia and Type 1 Diabetes despite Multiple Disease-Modifying Antirheumatic Drug Therapy That Was Successfully Treated with Baricitinib: A Novel Case Report - Yuya Fujita; Masao Nawata; Atsushi Nagayasu; Kazuki Someya; Kazuyoshi Saito; Yoshiya Tanaka (Case Reports in Rheumatology)
Baricitinib is a Janus kinase 1/2 (JAK1/2) inhibitor used in the treatment of rheumatoid arthritis. A 71-year-old woman with rheumatoid arthritis complicated by systemic sclerosis and type 1 diabetes that were resistant to multiple disease-modifying antirheumatic drugs started treatment with baricitinib. After baricitinib administration, the disease activity of her rheumatoid arthritis was attenuated from the early stage of treatment, and the effect was maintained for up to 52 weeks. In addition, the skin sclerosis in systemic sclerosis showed an improvement. Regarding the influence on type 1 diabetes, the required daily dose of insulin and hemoglobin A1c (HbA1c) levels decreased. To date, no studies have demonstrated the effectiveness of baricitinib on systemic sclerosis or type 1 diabetes. We report that baricitinib was effective for systemic sclerosis and type 1 diabetes, as well as for rheumatoid arthritis, for up to 52 weeks.